Unilateral Inguinal Swelling in a Young Female: An Unusual Presentation of MURCS - Navdeep Kaur; Bhawna Satija; Sayani Mahal; Shubham Arora (Journal of Human Reproductive Sciences)
Inguinal hernia in females is an uncommon entity. While most patients present in infancy or early in childhood, only a few cases are diagnosed in adulthood. Most cases of inguinal hernia have small bowel or omentum as its content. Herniation of the ovary or fallopian tube is rare. In our case, an 18-year-old female presented to the outpatient department with unilateral inguinal swelling, which on imaging was found to be ovarian inguinal herniation. This prompted further evaluation. There was an associated absence of the uterus and left kidney, and congenital block vertebrae involving the cervical spine. On probing it was found that she had primary amenorrhoea with normal secondary sexual characteristics. All the findings led to the diagnosis of Mayer Rokitansky Kuster Hauser type II or Mullerian duct aplasia renal agenesis cervicothoracic somite dysplasia (MURCS) with unilateral inguinal ovarian herniation. Mullerian duct aplasia renal agenesis cervicothoracic somite dysplasia (MURCS) present a challenge as they require a multidisciplinary team including gynaecologist, surgeon and psychologist to preserve the ovarian function and help the patient counsel regarding the reproductive outcome and wade through the associated emotional stress.